'Creating a modern nursing workforce': nursing education reform in the neoliberal social imaginary. Issue 2 (9th November 2020) - Snee, Helene; White, Peter; Cox, Nigel
Abstract: This paper explores how nursing education both exemplifies the contradictions of neoliberalism alongside its seemingly all-encompassing influence. We conduct a feminist critical policy analysis to trace the histories of nursing as a feminised vocation located outside the academy, and how this is reflected in recent policy. We then critically explore widening participation and social mobility in relation to nursing education, and demonstrate how a discourse of fairness is used to justify market solutions. The 'special case' of nursing is considered through an analysis of how 'the nurse' as subject is constituted in education policy discourse. Our discussion focuses on the effects of these reforms and demonstrates how historical discourses that centre on women as carers are assimilated into the 'neoliberal social imaginary'. The paper's scope is both local – the gendered history of nursing education in England – and global – the force of neoliberal globalisation in education policy.